Monitoring the Phenolic Ripening of Red Grapes Using a Multisensor System Based on Metal-Oxide Nanoparticles - Garcia-Hernandez, Celia; Medina-Plaza, Cristina; Garcia-Cabezon, Cristina; Blanco, Yolanda; Fernandez-Escudero, Jose A.; Barajas-Tola, Enrique; Rodriguez-Perez, Miguel A.; Martin-Pedrosa, Fernando; Rodriguez-Mendez, Maria L. (Frontiers in Chemistry, 2018)
The maturity of grapes is usually monitored by means of the sugar content. However, the assessment of other parameters such as the phenolic content is also important because the phenolic maturity has an important impact on the organoleptic characteristics of wines. In this work, voltammetric sensors able to detect the phenolic content of red grapes have been developed. They are based on metal oxide nanoparticles (CeO2, NiO and TiO2,) whose excellent electrocatalytic properties towards phenols allows obtaining sensors with detection limits in the range of 10-8 M and coefficients of variation lower than 7%. An electronic tongue constructed using a combination of the nanoparticle-based sensors is capable to monitor the phenolic maturity of red grapes from véraison to maturity. An advantage of this system is that the electronic tongue can be used for the simultaneous assessment of the total phenolic index, the sugar content and the acidity. Thus, the electronic tongue based on metal oxide nanoparticles can be a valuable tool to monitor the ripeness process.